Air-conditioning system with simultaneous control of sensible and latent heat for building energy conservation in Malaysia - Azizuddin, Abd Aziz (2014)
Buildings in tropical countries such as Malaysia are exposed to excessive amount of solar heat during daytime occupancy. In addition to that, the outdoor air contains excessive humidity due to the nature of the climate. Air-conditioning system is the main energy consumer of the buildings, more so with the requirement of the full 12 months cooling period in the country. The increasing demand of energy due to its status as a developing country puts Malaysia in a critical situation in terms of building sustainability. Another quandary associated with tropical environment is the indoor thermal comfort due to the high humidity. The usage of normal air-conditioning system means that the room has to be overcooled in order to bring down the humidity. Unfortunately, the low temperature set-point technique is neither comfort cautious nor energy friendly. There is an option to solve the humidity problems by the use of the outdoor air treatment system which neutralizes the incoming fresh air into the room. However, high equipment cost renders the system unfavorable in Malaysia. Therefore, the viable solution to the high latent load requires an innovative system that is affordable, runs at relatively low energy consumption yet be able to provide satisfactory indoor thermal comfort. In the research, a new air-conditioning approach termed Dual ABU (air handling unit) system is proposed to be the answer. The simplicity in arrangement and control setup ensures that the system can be reasonably priced. On top of that, it can be designed as an add-on configuration to the existing air-conditioning. The function of Latent AHU in the proposed system is to remove moisture from the conditioned room up to the desired humidity level and in the process the room temperature is also fractionally reduced. The Sensible AHU completes the task by removing the remaining sensible heat so that the room temperature is maintained at the required set-point. By reducing the relative humidity to 50%, a much lower value than that of the normal air-conditioning could offer, room temperature of the new system is shifted higher to 26°C in order to reduce the energy consumption. However, thermal comfort of the occupants has not been compromised. The performance of the proposed system is evaluated through simulation approach. The result shows that the new system could offer energy savings of between 10.2 to 13.6% in constant-air-volume configuration and between 10.7 to 13.2% in variable-air-volume configuration compared to normal air-conditioning system. The procedure to design of the proposed system using manual calculation and psychrometric chart is also being clarified. In addition, the possibility to retrofit the new system into existing air-conditioning system is explained at the end of the research.